Pengembangan Sistem Absensi Digital Guru Menggunakan RFID di SMK Khazanah Kebajikan: Design and Implementation of an RFID-Based Digital Attendance System for Teachers at SMK Khazanah Kebajikan - Istiyono, Yogi Priyo; Firasanto, Gaguk; Laksono, Pranoto Budi; Sunardi, Ariyawan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the efficiency and accuracy of teacher attendance management at SMK Khazanah Kebajikan by developing a web-based digital attendance system integrated with Radio Frequency Identification (RFID) technology. Previously, attendance was recorded manually using a logbook, which often resulted in data entry errors, delayed recap processes, and a lack of data transparency. The developed system utilizes PHP as the programming language, MySQL for the database, and hardware components such as RFID cards and readers. The implementation stages included needs analysis, system design, technology deployment, user training, and satisfaction evaluation. Results show that the system successfully records attendance automatically and in real time, simplifying attendance management and data recapitulation. User satisfaction surveys conducted with 20 teachers and staff revealed that 70% were delighted with the data accuracy, 65% with time efficiency, and 60% with ease of use. Additionally, the system's user interface and access speed received positive responses from most users. This system is expected to serve as a practical and replicable model for other schools facing similar challenges in managing teacher attendance and improving administrative transparency.